GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 7482 species occurrences available in GBIF matching the query: TaxonKey: Apodiformes Country: Australia Geometry: POLYGON((138.87 -80.12,138.87 80.12,-140.27 80.12,-140.27 -80.12,138.87 -80.12)) HasGeospatialIssue: false. The dataset includes 7482 records from 22 constituent datasets: 34 records from OEH Atlas of NSW Wildlife. 41 records from Australian National Wildlife Collection provider for OZCAM. 4 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 1812 records from Fauna Atlas N.T.. 26 records from Museum Victoria provider for OZCAM. 810 records from SA Fauna (BDBSA). 874 records from Historical Bird Atlas. 1706 records from BirdLife Australia, Birdata. 2 records from Museum of Comparative Zoology, Harvard University. 775 records from EOD - eBird Observation Dataset. 2 records from naturgucker. 1099 records from First Bird Atlas. 23 records from Northern Territory Museum and Art Gallery provider for OZCAM. 125 records from Western Australian Museum provider for OZCAM. 15 records from Natural History Museum (London) Collection Specimens. 2 records from UWBM Ornithology Collection. 2 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 1 records from Queensland Museum provider for OZCAM. 5 records from UMMZ Birds Collection. 8 records from Australian Museum provider for OZCAM. 6 records from MVZ Bird Collection (Arctos). 110 records from South Australian Museum Australia provider for OZCAM. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences